Improving Students’ Writing Ability Through Concept Sentence Method - Dewi, Rino Sinta (National Multidisciplinary Sciences, 2023)
: Teachers need to use appropriate learning method to help students achieve the purpose of learning, especially in learning writing. The study aims to describe how Concept Sentence Method through a small group discussion improve students writing ability of senior high school students of Muhammadiyah 3 Jember. Classroom Action Research (CAR) was implemented using a design by Kurt Lewin to the XI grade students; 5 males and 12 females. It was done in two cycles; each of which consisted of two meetings. The researcher did collaborative action with the class teacher. The data collection involved writing test in two cycles and writing scoring rubric which evaluated content, organization, vocabulary, language use/grammar, and mechanics. The study used 78 as the criteria of success of the students’ writing. The finding showed the class’s mean score of cycle one was 77.23 and on the cycle two reached up to 80.41. Therefore, the criteria of success were achieved, it can be seen from the students’ action when the method was implemented. Students were actively taking part in the discussion and share their ideas to other.